Crown ether grafted polymer as well as preparation method and application thereof
By introducing crown ether groups into polybenzimidazole (PBI) polymers, the problem of proton transfer obstruction caused by strong molecular chain interactions is solved, and the electrochemical performance of all vanadium flow batteries is improved.
Patent Information
- Application Number
- CN202411927268.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
When polybenzimidazole (PBI) polymers act as ion-conducting membranes in all vanadium flow cells, proton transfer is blocked due to strong interactions of molecular chains, which affects electrochemical performance.
The crown ether group is introduced on the molecular chain of polybenzimidazole (PBI) polymers, and the crown ether grafted polymer is prepared by reflux reaction to improve the ionic conductivity of the ionic conductive film.
By introducing crown ether groups, the accumulation of polymer chains is reduced, the proton transfer capacity is improved, and the electrochemical performance of all vanadium flow batteries is significantly improved.
Smart Images

Figure CN119735809A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion conduction membranes, and in particular relates to a crown ether grafted polymer and a preparation method and application thereof. Background Art
[0002] All-vanadium redox flow batteries (VRFBs) have attracted widespread attention due to their energy and power decoupling, long service life and excellent safety. The ion conduction membrane is one of the core components of the all-vanadium flow battery. It can not only block the positive and negative active substances to prevent cross-contamination and self-discharge; it can also transfer balance ions to maintain the charge balance between the positive and negative electrodes. The performance of the ion conduction membrane greatly affects the performance of the battery. The selectivity of the ion conduction membrane will affect the coulombic efficiency and capacity retention rate of the battery, while its ion conductivity will affect the voltage efficiency of the battery. Therefore, an ideal ion conduction membrane should have both high ion conductivity and high selectivity. In addition, the ion conduction membrane also needs to have sufficient mechanical strength and chemical stability to withstand the impact of the electrolyte during operation, the strong acidity of the electrolyte, and the active substance VO2 + Strong oxidizing properties.
[0003] Polybenzimidazole (PBI) polymers are the most commonly used polymer materials for ion-conducting membranes of VRFBs because of their excellent stability and ability to be protonated in strong acid environments to hinder the penetration of vanadium ions. However, the strong interaction between PBI molecular chains causes the polymer chains to stack tightly, which seriously hinders the transfer of protons, thereby affecting the electrochemical performance of VRFBs. Therefore, how to further improve the performance of polybenzimidazole (PBI) polymers is of great significance to further improve the comprehensive performance of VRFBs. Summary of the invention
[0004] The purpose of the present invention is to provide a crown ether grafted polymer and its preparation method and application. The present invention can effectively improve the ion conductivity of the polybenzimidazole (PBI) type ion conductive membrane by introducing a crown ether group into the polymer chain of the polybenzimidazole (PBI) type polymer, thereby improving the electrochemical performance of the all-vanadium redox flow battery.
[0005] In the first aspect, the present invention provides a crown ether grafted polymer, which adopts the following technical scheme: A crown ether grafted polymer, with a polybenzimidazole (PBI) polymer as a matrix and a crown ether group as a grafted group; the structural formula is one of formulas Ⅰ to VI: Wherein: R represents a crown ether group, and the crown ether group is one of formulas VII to XI: .
[0006] In a second aspect, the present invention provides a method for preparing a crown ether grafted polymer, comprising the following steps: A polybenzimidazole (PBI) polymer is dissolved in a solvent to obtain a polymer solution; a chlorine-substituted crown ether and a catalyst are added to the polymer solution, and a reflux reaction is performed under an inert atmosphere, and after the reaction is completed, a crown ether-grafted polymer is obtained; Wherein: the structural formula of the polybenzimidazole (PBI) polymer is one of Formulas 1 to 6: The structural formula of the chlorine-substituted crown ether is one of Formulas 7 to 11: .
[0007] Preferably, the solvent is one or both of dimethyl sulfoxide and N,N-dimethylacetamide, and the mass fraction of the polybenzimidazole (PBI) polymer in the solvent is 2.5-3.5wt%.
[0008] Preferably, the molar ratio of the repeating unit of the polybenzimidazole (PBI) polymer to the chlorine-substituted crown ether is 1:(0.7-0.9).
[0009] The repeating unit of polybenzimidazole (PBI) polymers is the structural formula in brackets, that is, the structural formula of polybenzimidazole (PBI) polymers is , whose repeating unit is .
[0010] Preferably, the catalyst is one or both of lithium carbonate and lithium hydroxide; the mass of the catalyst is 18-20% of the mass of the polybenzimidazole (PBI) polymer.
[0011] Preferably, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0012] Preferably, the temperature of the reflux reaction is 90-110° C., and the time of the reflux reaction is 36-72 h.
[0013] In a third aspect, the present invention provides an ion conducting membrane prepared by using the aforementioned crown ether grafted polymer.
[0014] A fourth aspect is a method for preparing an ion conducting membrane, comprising the following steps: S1: Casting a film casting solution containing a crown ether grafted polymer and polyethyleneimine into a film to obtain a base film; S2: The basement membrane is sequentially treated as follows: Soak in hot water; Soak in acid solution; Wash to neutral; obtaining a treated basement membrane; S3: Soaking the treated base membrane in an acid solution to absorb acid, thereby obtaining an ion conducting membrane.
[0015] Preferably, in step S1, the mass ratio of the crown ether grafted polymer to polyethyleneimine is 1:0.7-0.9; and the casting temperature is 70-90°C.
[0016] Preferably, in step S1, the casting solution containing the crown ether grafted polymer and polyethyleneimine is prepared by dissolving the crown ether grafted polymer in a solvent, then adding polyethyleneimine under an inert atmosphere, stirring and dissolving to obtain the casting solution.
[0017] Further preferably, the solvent is one or both of dimethyl sulfoxide and N,N-dimethylacetamide; the mass fraction of the crown ether grafted polymer in the solvent is 0.8-1.2wt%; and the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0018] Preferably, in step S2, the temperature of the hot water is 70-90°C; the base film is immersed in the hot water for 3-5 hours; the acid solution is a sulfuric acid solution, the concentration of the acid solution is 0.4-0.6 mol / L, and the base film is immersed in the acid solution for 3-5 hours.
[0019] Preferably, in the step S2, after washing to neutrality and before obtaining the treated base film, the step further includes: soaking in alkaline solution and washing to neutrality.
[0020] Further preferably, the alkali solution is one of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate, and lithium carbonate solution, and the concentration of the alkali solution is 1.5-3 mol / mL; the basement membrane is immersed in the alkali solution for 36-72 hours.
[0021] Preferably, in step S3, the acid solution is a sulfuric acid solution, the concentration of the acid solution is 2-4 mol / L, and the acid absorption time is 18-36 h.
[0022] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: The present invention grafts part of the crown ether groups on the molecular chain of the polybenzimidazole (PBI) polymer. The crown ether itself has a large-size structure, which can reduce the stacking of the molecular chain of the polybenzimidazole (PBI) polymer. At the same time, the crown ether is a hydrophilic group with the ability to transfer protons. The crown ether group is introduced into the molecular chain of the polybenzimidazole (PBI) polymer, which can improve the ion conductivity of the polybenzimidazole ion conduction membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1Infrared spectra of the ion conducting membranes prepared in Example 1 and Example 3.
[0024] Figure 2 The XRD spectra of the ion conductive membranes prepared in Example 1, Example 3 and Comparative Example 1 are shown.
[0025] Figure 3 The figures are scanning electron microscope images of the membrane cross-section and surface of the ion conductive membranes prepared in Examples 1 and 2; (a) and (b) are the cross-sectional SEM image and surface SEM image of the ion conductive membrane prepared in Example 1, respectively; (c) and (d) are the cross-sectional SEM image and surface SEM image of the ion conductive membrane prepared in Example 2, respectively.
[0026] Figure 4 The ion-conducting membranes prepared in Example 1 and Comparative Example 1 are used in all-vanadium liquid flow batteries. The coulombic efficiency of the batteries at different current densities ( Figure 4 a) Voltage efficiency ( Figure 4 b) and energy efficiency ( Figure 4 c) Data graph. DETAILED DESCRIPTION
[0027] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0028] As mentioned above, in the first aspect, the present invention provides a crown ether grafted polymer, using the following technical solution: A crown ether grafted polymer, with a polybenzimidazole (PBI) polymer as a matrix and a crown ether group as a grafted group; the structural formula is one of formulas Ⅰ to VI: Wherein: R represents a crown ether group, and the crown ether group is one of formulas VII to XI: .
[0029] Some crown ether groups are grafted onto the molecular chains of polybenzimidazole (PBI) polymers. The crown ether itself has a large-size structure, which can reduce the stacking of the molecular chains of polybenzimidazole (PBI) polymers. At the same time, the crown ether is a hydrophilic group with the ability to transfer protons. Introducing the crown ether group into the molecular chain of polybenzimidazole (PBI) polymers can improve the ionic conductivity of the polybenzimidazole ion conduction membrane.
[0030] In a second aspect, the present invention provides a method for preparing a crown ether grafted polymer, comprising the following steps: A polybenzimidazole (PBI) polymer is dissolved in a solvent to obtain a polymer solution; a chlorine-substituted crown ether and a catalyst are added to the polymer solution, and a reflux reaction is performed under an inert atmosphere, and after the reaction is completed, a crown ether-grafted polymer is obtained; Wherein: the structural formula of the polybenzimidazole (PBI) polymer is one of Formulas 1 to 6: The structural formula of the chlorine-substituted crown ether is one of Formulas 7 to 11: .
[0031] Preferably, the solvent is one or both of dimethyl sulfoxide and N,N-dimethylacetamide, and the mass fraction of the polybenzimidazole (PBI) polymer in the solvent is 2.5-3.5 wt%.
[0032] Preferably, the molar ratio of the repeating unit of the polybenzimidazole (PBI) polymer to the chlorine-substituted crown ether is 1:(0.7-0.9).
[0033] Preferably, the catalyst is one or both of lithium carbonate and lithium hydroxide; the mass of the catalyst is 18-20% of the mass of the polybenzimidazole (PBI) polymer.
[0034] Preferably, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0035] Preferably, the temperature of the reflux reaction is 90-110° C., and the time of the reflux reaction is 36-72 h.
[0036] In a third aspect, the present invention provides an ion conducting membrane prepared by using the aforementioned crown ether grafted polymer.
[0037] A fourth aspect is a method for preparing an ion conducting membrane, comprising the following steps: S1: Casting a film casting solution containing a crown ether grafted polymer and polyethyleneimine into a film to obtain a base film; S2: The basement membrane is sequentially treated as follows: Soak in hot water; Soak in acid solution; Washing to neutrality to obtain the treated base film; S3: Soaking the treated base membrane in an acid solution to absorb acid, thereby obtaining an ion conducting membrane.
[0038] Preferably, in step S1, the mass ratio of the crown ether grafted polymer to polyethyleneimine is 1:0.7-0.9; and the casting temperature is 70-90°C.
[0039] Preferably, in step S1, the casting solution containing the crown ether grafted polymer and polyethyleneimine is prepared by dissolving the crown ether grafted polymer in a solvent, then adding polyethyleneimine under an inert atmosphere, stirring and dissolving to obtain the casting solution.
[0040] Further preferably, the solvent is one or both of dimethyl sulfoxide and N,N-dimethylacetamide; the mass fraction of the crown ether grafted polymer in the solvent is 0.8-1.2 wt %; and the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0041] Preferably, in the step S2, after washing to neutrality and before obtaining the treated base film, the step further includes: soaking in alkaline solution and washing to neutrality.
[0042] Further preferably, the alkali solution is one of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate, and lithium carbonate solution, and the concentration of the alkali solution is 1.5-3 mol / mL; the basement membrane is immersed in the alkali solution for 36-72 hours.
[0043] In the preparation process of the ion conducting membrane of the present invention, an alkali solution is used for soaking treatment; OH in the alkali solution - The hydrogen atoms on the imidazole ring in the polybenzimidazole polymer will be removed to form negatively charged nitrogen atoms; the interaction between the negatively charged nitrogen atoms and the alkali metal ions (such as sodium ions and lithium ions) in the solution will reduce the distance between the molecular chains of the polybenzimidazole membrane, significantly improving the ion selectivity of the membrane. At the same time, since the crown ether is grafted on the polybenzimidazole polymer, the crown ether itself has a large-size structure, which will control the reduction of the distance between the molecular chains of the polybenzimidazole polymer within a certain range; and the crown ether, as a hydrophilic group, has the ability to transfer protons, which will keep the ion conductivity of the ion conduction membrane at a high level. Therefore, through the mutual restraint of crown ether grafting treatment and alkali treatment, the ion conduction membrane can have both high ion conductivity and high selectivity; thereby significantly improving the electrochemical performance of the flow battery.
[0044] Preferably, in step S2, the temperature of the hot water is 70-90°C; the base film is immersed in the hot water for 3-5 hours; the acid solution is a sulfuric acid solution, the concentration of the acid solution is 0.4-0.6 mol / L, and the base film is immersed in the acid solution for 3-5 hours.
[0045] Preferably, in step S3, the acid solution is a sulfuric acid solution, the concentration of the acid solution is 2-4 mol / L, and the acid absorption time is 18-36 h.
[0046] The molecular weight of polyethyleneimine used in the embodiment of the present invention is 600Da, and the structural formula is as follows: .
[0047] Example 1 The synthetic route of the crown ether grafted polymer of this embodiment is as follows: The specific preparation method is as follows: 1g of polybenzimidazole polymer (as shown in Formula 5, molecular weight 4.72×10 5 Da, repeating unit 1180) was dissolved in 30mL DMSO to obtain a transparent solution; 0.646g 4'-chloromethylbenzo 15 crown 5 ether (as shown in Formula 7) and 0.19g lithium carbonate were added to the transparent solution, and then refluxed at 100°C for 48h under a nitrogen atmosphere. After the reaction was completed, the reaction solution was poured into deionized water, and after complete precipitation, it was filtered. After the filter cake was washed and dried, a crown ether grafted polybenzimidazole polymer (as shown in Formula V-1) was obtained. Wherein: the molar ratio of the repeating unit of the polybenzimidazole polymer to 4'-chloromethylbenzo 15 crown 5 ether was 1:0.8.
[0048] The preparation method of the ion conducting membrane is as follows: (1) At 80°C, 0.2 g of a crown ether grafted polybenzimidazole polymer (shown in Formula V-1) was dissolved in 20 mL of DMSO to obtain a uniform transparent solution. Under nitrogen protection, 0.177 g of polyethyleneimine was added to the uniform transparent solution, and then stirred at 500 rpm for 48 h to obtain a casting solution; the casting solution was cast into a film at 80°C to obtain a base film.
[0049] (2) The base film is soaked in deionized water at 80° C. for 4 hours, and then soaked in a sulfuric acid solution with a concentration of 0.5 mol / L for 4 hours; after soaking, the base film is washed with deionized water until the washing water is neutral, thereby obtaining an acid-treated base film.
[0050] (3) The acid-treated base film is soaked in a 2 mol / L sodium hydroxide solution for 48 hours. After soaking, the treated base film is washed with deionized water until the washing water becomes neutral, thereby obtaining an alkali-treated base film.
[0051] (4) The base membrane after the alkali treatment was immersed in a sulfuric acid solution with a concentration of 3 mol / L for 24 hours to absorb the acid, thereby obtaining an ion conductive membrane S1.
[0052] Example 2 The method is basically the same as Example 1, except that in step (3) of the method for preparing the ion conductive membrane, 2 mol / L lithium hydroxide solution is used to replace 2 mol / L sodium hydroxide solution; and the ion conductive membrane S2 is prepared accordingly.
[0053] Comparative Example 1 Without crown ether grafting, the ion conducting membrane DS1 is prepared directly using the polybenzimidazole polymer (as shown in Formula 5) according to the preparation method of the ion conducting membrane in Example 1.
[0054] Example 3 The method is basically the same as Example 1, except that in the method for preparing the ion conductive membrane, step (3) is omitted, that is, no alkali treatment is performed, and the ion conductive membrane S3 is prepared accordingly.
[0055] Example 4 The synthetic route of the crown ether grafted polymer of this embodiment is as follows: The specific preparation method is as follows: 1g of polybenzimidazole polymer (as shown in Formula 4, molecular weight is 4.72×10 5 Da, repeating unit 1200) was dissolved in 30mL DMF to obtain a uniform transparent solution; 0.643g 4'-chloromethylbenzo 18 crown 6 ether (as shown in Formula 9) and 0.2g lithium carbonate were added to the uniform transparent solution, and then refluxed at 110°C for 36h under a nitrogen atmosphere. After the reaction was completed, the reaction solution was poured into deionized water, and after complete precipitation, it was filtered. After the filter cake was washed and dried, a crown ether grafted polybenzimidazole polymer (as shown in Formula IV-1) was obtained. Wherein: the molar ratio of the repeating unit of the polybenzimidazole polymer to 4'-chloromethylbenzo 18 crown 6 ether was 1:0.7.
[0056] The preparation method of the ion conducting membrane is as follows: (1) At 80°C, 0.2 g of a crown ether grafted polybenzimidazole polymer (shown in Formula IV-1) was dissolved in 20 mL of DMF to obtain a uniform transparent solution. Under nitrogen protection, 0.170 g of polyethyleneimine was added to the uniform transparent solution, and then stirred at 500 rpm for 48 h to obtain a casting solution; the casting solution was cast into a film at 90°C to obtain a base film.
[0057] (2) The base film is soaked in deionized water at 90°C for 4 hours, and then soaked in a sulfuric acid solution with a concentration of 0.6 mol / L for 3 hours; after soaking, the base film is washed with deionized water until the washing water is neutral, thereby obtaining an acid-treated base film.
[0058] (3) The acid-treated base film is immersed in a 3 mol / L sodium hydroxide solution for 36 hours. After immersion, the treated base film is washed with deionized water until the washing water becomes neutral, thereby obtaining an alkali-treated base film.
[0059] (4) The base membrane after the alkali treatment was immersed in a sulfuric acid solution with a concentration of 3 mol / L for 24 hours to absorb the acid, thereby obtaining an ion conductive membrane S4.
[0060] Example 5 The synthetic route of the crown ether grafted polymer of this embodiment is as follows: The specific preparation method is as follows: 1g of polybenzimidazole polymer (as shown in Formula 2, molecular weight is 4.46×10 5 Da, repeating unit 1320) was dissolved in 30mL DMSO to obtain a uniform transparent solution; 0.729g 4'-chloromethylbenzo 12 crown 4 ether (as shown in Formula 8) and 0.20g lithium carbonate were added to the uniform transparent solution, and then refluxed at 90°C for 60h under a nitrogen atmosphere. After the reaction was completed, the reaction solution was poured into deionized water, and after complete precipitation, it was filtered. After the filter cake was washed and dried, a crown ether grafted polybenzimidazole polymer (as shown in Formula II-1) was obtained. Wherein: the molar ratio of the repeating unit of the polybenzimidazole polymer to 4'-chloromethylbenzo 12 crown 4 ether was 1:0.9.
[0061] The preparation method of the ion conducting membrane is as follows: (1) At 80°C, 0.2 g of a crown ether grafted polybenzimidazole polymer (shown in Formula II-1) was dissolved in 20 mL of DMSO to obtain a uniform transparent solution. Under nitrogen protection, 0.180 g of polyethyleneimine was added to the uniform transparent solution, and then stirred at 500 rpm for 48 h to obtain a casting solution; the casting solution was cast into a film at 70°C to obtain a base film.
[0062] (2) The base film is soaked in deionized water at 70° C. for 5 h, and then soaked in a sulfuric acid solution with a concentration of 0.4 mol / L for 5 h. After soaking, the base film is washed with deionized water until the washing water becomes neutral, thereby obtaining an acid-treated base film.
[0063] (3) The acid-treated base film is immersed in a potassium hydroxide solution having a concentration of 1.5 mol / L for 36 hours. After immersion, the treated base film is washed with deionized water until the washing water becomes neutral, thereby obtaining an alkali-treated base film.
[0064] (4) The base membrane after the alkali treatment was immersed in a sulfuric acid solution with a concentration of 3 mol / L for 24 hours to absorb the acid, thereby obtaining an ion conductive membrane S5.
[0065] Example 6 The synthetic route of the crown ether grafted polymer of this embodiment is as follows: The specific preparation method is as follows: 1 g of polybenzimidazole polymer (as shown in Formula 6, molecular weight 5.97×10 5 Da, repeating unit 1180) was dissolved in 30mL DMSO to obtain a uniform transparent solution; 0.723g 4'-chloromethylbenzo 24 crown 8 ether (as shown in Formula 11) and 0.2g lithium carbonate were added thereto, and then refluxed at 90°C for 60h under a nitrogen atmosphere. After the reaction was completed, the reaction solution was poured into deionized water, and after complete precipitation, it was filtered. After the filter cake was washed and dried, a crown ether grafted polybenzimidazole polymer (as shown in Formula VI-1) was obtained. Wherein: the molar ratio of the repeating unit of the polybenzimidazole polymer to 4'-chloromethylbenzo 24 crown 8 ether was 1:0.9.
[0066] The preparation method of the ion conducting membrane is as follows: (1) At 80°C, 0.2 g of a crown ether grafted polybenzimidazole polymer (shown in Formula VI-1) was dissolved in 20 mL of DMSO to obtain a uniform transparent solution. Under nitrogen protection, 0.165 g of polyethyleneimine was added to the uniform transparent solution, and then stirred at 500 rpm for 48 h to obtain a casting solution; the casting solution was cast into a film at 80°C to obtain a base film.
[0067] (2) The base film is soaked in deionized water at 80° C. for 4 hours, and then soaked in a sulfuric acid solution with a concentration of 0.5 mol / L for 4 hours; after soaking, the base film is washed with deionized water until the washing water is neutral, thereby obtaining an acid-treated base film.
[0068] (3) The acid-treated base film is soaked in a 2 mol / L potassium hydroxide solution for 18 h. After soaking, the treated base film is washed with deionized water until the washing water becomes neutral, thereby obtaining an alkali-treated base film.
[0069] (4) The base membrane after the alkali treatment was immersed in a sulfuric acid solution with a concentration of 3 mol / L for 24 hours to obtain an ion conductive membrane S6.
[0070] The ion conducting membranes prepared in Example 1 and Example 3 were tested by infrared spectroscopy. The results show that Figure 1 There is no substantial difference in the infrared spectra of the two, indicating that the chemical structures of the ion-conducting membranes in Example 1 and Example 3 are the same, and the alkaline solution treatment will not cause the chemical structure of the membrane to change.
[0071] The XRD spectra of the ion conducting membranes prepared in Example 1, Example 3 and Comparative Example 1 are as follows: Figure 2 As shown, it can be seen that there is a difference in 2θ angle in the XRD spectra of the ion conductive membranes prepared in Example 1 and Example 3, indicating that the alkali solution treatment will change the crystal structure of the ion conductive membrane. The XRD spectra of the ion conductive membranes prepared in Example 1 and Comparative Example 1 are quite different, indicating that the crystal structure of polybenzimidazole has also changed after the crown ether is grafted.
[0072] The cross-section and surface scanning electron microscope images of the ion conducting membranes prepared in Example 1 and Example 2 are as follows: Figure 3 As shown, it can be seen that the structures of the ion conductive membranes prepared in Example 1 and Example 2 are relatively uniform and dense. Due to the strong interaction between the nitrogen of the imidazole group, the polybenzimidazole molecular chains are stacked. If pure PBI is used for film casting, the density of the membrane will be very high, and the ion conductivity of the pure PBI membrane will be poor. In order to improve the ion conductivity of the PBI membrane, polyethyleneimine (PEI) is generally added to the casting solution. PEI can form hydrogen bonds with N on the imidazole of polybenzimidazole, breaking the original stacking mode of the PBI molecular chain, increasing the chain spacing, and expanding the ion transmission. Therefore, the addition of PEI can improve the ion transmission channel of PBI, but the structure of the ion conductive membrane is still relatively dense.
[0073] Performance Test: The ion-conducting membranes prepared in Examples 1 to 6 and Comparative Example 1 were assembled in an all-vanadium liquid flow battery, and the performance of the battery was tested. The specific assembly method is: using a graphite plate as a current collector, activated carbon felt as an electrode, epoxy resin as an end plate, and using a polytetrafluoroethylene plate to fix the ion-conducting membrane between the two end plates to form a liquid flow battery; using a polytetrafluoroethylene tube to connect a single cell, an electrolyte storage tank, and a peristaltic pump to form a complete liquid flow battery device.
[0074] The specific test method is: deionized water as solvent, 3 mol / L sulfuric acid solution as supporting electrolyte, 1.5 mol / L VO 2+ / VO2 + and 1.5 mol / L V 2+ / V 3+ The positive and negative redox active pairs constitute the electrolyte. The battery performance was monitored using a blue electric tester, with the charge and discharge cut-off voltage set at 0.8~1.65 V and the current density at 200mA / cm 2 During the test, the electrolyte was protected by nitrogen.
[0075] The ion-conducting membranes prepared in Example 1 and Comparative Example 1 are applied to all-vanadium liquid flow batteries. The performance diagram of the batteries can be seen as follows: Figure 4 ; The specific test data of Examples 1 to 6 and Comparative Example 1 can be seen in Table 1.
[0076] Table 1: Ion-conducting membranes prepared in Examples and Comparative Examples are applied to flow batteries, and battery performance parameters from Figure 4 As can be seen from Table 1, the energy efficiency of the flow battery prepared by the ion conductive membrane S1 in Example 1 is significantly higher than that in Comparative Example 1, indicating that the use of crown ether grafted polybenzimidazole can improve the energy efficiency of the flow battery. In Example 2, lithium hydroxide solution is used to replace the sodium hydroxide in Example 1 during the alkali treatment process, and it can be seen that its energy efficiency will decrease to a certain extent, but still maintains a good energy efficiency.
[0077] It can be seen from the data in Table 1 that compared with Example 1, the ion conduction membrane of Example 3 is not subjected to alkali treatment, and the energy efficiency is somewhat lower than that of Example 1, but the energy efficiency is somewhat improved compared with that of Comparative Example 1.
[0078] It can be seen from the data in Table 1 that Examples 4 to 6 mainly use different types of crown ether grafted polybenzimidazole polymers and change the process parameters of the preparation process of the ion conduction membrane. The energy efficiency of the corresponding liquid flow batteries has a certain degree of change, but is still above 80%.
[0079] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A crown ether grafted polymer, characterized in that It uses polybenzimidazole polymer as the matrix and crown ether group as the grafting group; the structural formula is one of formulas Ⅰ to VI: Wherein: R represents a crown ether group, and the crown ether group is one of formulas VII to XI: 。 2. A method for preparing a crown ether grafted polymer according to claim 1, characterized in that: The following steps are involved: The polybenzimidazole polymer is dissolved in a solvent to obtain a polymer solution; a chlorine-substituted crown ether and a catalyst are added to the polymer solution, and a reflux reaction is performed under an inert atmosphere, and after the reaction is completed, a crown ether-grafted polymer is obtained; Wherein: the structural formula of the polybenzimidazole polymer is one of Formulas 1 to 6: ; The structural formula of the chlorine-substituted crown ether is one of Formulas 7 to 11: 。 3. The method for preparing a crown ether grafted polymer according to claim 2, characterized in that: The molar ratio of the repeating unit of the polybenzimidazole polymer to the chlorine-substituted crown ether is 1:(0.7-0.9); The catalyst is one or both of lithium carbonate and lithium hydroxide; The mass of the catalyst is 18-20% of the mass of the polybenzimidazole polymer.
4. The method for preparing a crown ether grafted polymer according to claim 2, characterized in that: The inert atmosphere is a nitrogen atmosphere or an argon atmosphere; the temperature of the reflux reaction is 90-110° C.; and the time of the reflux reaction is 36-72 hours.
5. An ion conducting membrane, characterized in that The polymer is prepared by using the crown ether grafted polymer described in claim 1.
6. A method for preparing an ion conducting membrane according to claim 5, characterized in that: The following steps are involved: S1: Casting a film casting solution containing a crown ether grafted polymer and polyethyleneimine into a film to obtain a base film; S2: The basement membrane is sequentially treated as follows: Soak in hot water; Soak in acid solution; Wash to neutral; obtaining a treated basement membrane; S3: Soaking the treated base membrane in an acid solution to absorb acid, thereby obtaining an ion conducting membrane.
7. The method for preparing an ion conducting membrane according to claim 6, characterized in that: In the step S1, the mass ratio of the crown ether grafted polymer to polyethyleneimine is 1:0.7-0.9; and the film casting temperature is 70-90°C.
8. The method for preparing an ion conducting membrane according to claim 6, characterized in that: In step S2, the temperature of the hot water is 70-90°C; the base film is immersed in the hot water for 3-5 hours; the acid solution is a sulfuric acid solution, the concentration of the acid solution is 0.4-0.6 mol / L, and the base film is immersed in the acid solution for 3-5 hours.
9. The method for preparing an ion conducting membrane according to claim 6 or 8, characterized in that: In the step S2, after washing to neutrality and before obtaining the treated base film, the method further includes the steps of soaking in alkaline solution and washing to neutrality; wherein the alkaline solution is one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate, and lithium carbonate solution, and the concentration of the alkaline solution is 1.5-3 mol / mL; and the base film is soaked in the alkaline solution for 36-72 hours.
10. The method for preparing an ion conducting membrane according to claim 6, characterized in that: In step S3, the acid solution is a sulfuric acid solution, the concentration of the acid solution is 2-4 mol / L, and the acid absorption time is 18-36 hours.
Citation Information
Patent Citations
Imidazole type side chain polybenzimidazole membrane and preparation method and application thereof
CN111916806A
Preparation method of crown ether-containing copolymerized polyimide and phosphoric acid-doped proton exchange membrane prepared from same
CN113321807A
Preparation method of polybenzimidazole polymer porous membrane regulated and controlled by organic molecular template
CN118420965A
Dendrimer compositions with high branching multiplicity
US20060264530A1
Lithium ion batteries
US20130071742A1